2013
DOI: 10.1371/journal.pone.0060177
|View full text |Cite
|
Sign up to set email alerts
|

Wilm's Tumor-1 Protein Levels in Urinary Exosomes from Diabetic Patients with or without Proteinuria

Abstract: BackgroundPodocyte injury is an early feature of diabetic nephropathy (DN). Recently, urinary exosomal Wilm's tumor-1 protein (WT1), shed by renal epithelial cells, has been proposed as a novel biomarker for podocyte injury. However, its usefulness as biomarker for early diabetic nephropathy has not been verified yet. We investigated urinary exosomal WT1 in type-1 diabetic patients to confirm its role as a non-invasive biomarker for predicting early renal function decline.MethodsThe expression of WT1 protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(118 citation statements)
references
References 24 publications
1
117
0
Order By: Relevance
“…WT-1 expression in uEXs was also found to be increased in patients with diabetes. 85 Exosomal WT-1 was detected in all patients with diabetes and proteinuria but only one half of those without proteinuria and only 1 of 25 healthy controls. Expression of WT-1 in uEXs also correlated significantly with decline in kidney function.…”
Section: Glomerular Diseasementioning
confidence: 94%
“…WT-1 expression in uEXs was also found to be increased in patients with diabetes. 85 Exosomal WT-1 was detected in all patients with diabetes and proteinuria but only one half of those without proteinuria and only 1 of 25 healthy controls. Expression of WT-1 in uEXs also correlated significantly with decline in kidney function.…”
Section: Glomerular Diseasementioning
confidence: 94%
“…Exosomes, although distinct from MPs, have been identified in urine samples and proposed as tools for the noninvasive identification of renal pathology. 14,15 Using electron microscopy, Pascual et al 12 identified 100-to 200-nm urinary vesicles containing the complement receptor-1 consistent with podocyte MPs. Subsequent studies have further confirmed the presence of MPs in human urine.…”
mentioning
confidence: 99%
“…One study found that WT-1 in uEVs was increased in patients with focal segmental glomerulosclerosis but not in patients with AKI or in healthy volunteers (81,82); this finding, however, was not confirmed by others (37). The increase in uEV WT-1 was also associated with a decline in kidney function in diabetic nephropathy, suggesting early podocyte damage (33). Another podocyte injury marker is podocalyxin, which, unlike WT-1, was found in shedding vesicles (no expression of CD24 and CD63) (24,25).…”
Section: Use Of Uevs In Nephrologymentioning
confidence: 95%